ACUTE MESENTERIC ISCHEMIA: CLINICAL PICTURE, DIAGNOSIS AND TREATMENT. - Moreschi , Igor (2023)
Introduction: Acute Mesenteric Ischemia (AMI) is a rare pathology with a nonspecific clinical presentation, so that, in general, the diagnosis is late, a fact that compromises the implementation of adequate treatment. This pathology has several etiologies and commonly affects the elderly population, a fact that increases the concern of the health system, since in the current Brazilian scenario we have an inversion of the age pyramid and an increase in the senile population. Therefore, it is essential to understand the clinical nature of this medical emergency, as well as the diagnostic criteria and therapeutic basis, in order to ensure the best management of the case and the best prognosis for the patient. Thus, the main objective of this work is to carry out a review of the main clinical, diagnostic and therapeutic parameters of AMI. Methodology: This is a narrative review of the literature, which was carried out through a search on the PUBMED targeting platform using the descriptions joined by the AND operator: "Mesenteric Ischemia", "Diagnosis", "Therapeutics", “Surgical Procedures, Operative ”. We obtained 196 articles indexed in MEDLINE databases, which were submitted to the following inclusion criteria: published within 5 years, full text available in full and original study. After that, of the 14 articles found, 5 were excluded after reading the title and abstract because they did not fit the desired standards. The search and analysis of the articles was carried out in pairs, independently and blindly, there was no disagreement between the authors and after excluding duplicates, 7 articles were used in this review. Results and Discussion: For clinical suspicion, it is essential to be aware of the typical clinical features of the disease, with abdominal pain that is disproportionate to the physical examination. some specific etiologies bleeding. In general, laboratory tests have little value in terms of diagnostic criteria or exclusion of the disease, imaging tests being fundamental, with a main indication for tomography, in view of the limitations of ultrasound. The treatment consists of several parts, being essential to replace the volume, start empiric antibiotic therapy and revascularize the patient, as well as follow the treatment with drugs to prevent relapses. Conclusion: Understanding this pathology is essential to make an early diagnosis and determine the best intervention and ensure lower morbidity and mortality.